Influence of Pseudo-Potential Approximation in Temperature Dependence of Residual Electrical Resistivity of Cu-Au - Laz , Ezenwaka; Laz , Ezenwaka; N.S. , Umeokwonna (African Journal of Education,Science and Technology (AJEST), 2013)
Pseudo-potential form factors developed by Animalu in 1973 were used to re-examine the problems of temperature dependence of residual electrical resistivity of Cu-Au system in the light of state of distortion and thermal vibration of the lattice along with the short-range-order of atoms above critical temperature. The Ziman‟s formula for resistivity obtained yields a unified version for the calculation of resistivity in Pseudo-potential approximation. In this framework, the temperature dependence of the quantity Δρ/ρ for Cu-Au system was found to be in better agreement with the experimental data as compared to previous calculation